2019
DOI: 10.1097/dad.0000000000001259
|View full text |Cite
|
Sign up to set email alerts
|

Utility of TERT Promoter Mutations for Cutaneous Primary Melanoma Diagnosis

Abstract: Telomerase reverse transcriptase (TERT) promoter mutations are commonly found in malignant melanomas but rare in melanocytic nevi. To assess its potential diagnostic utility for the distinction of melanoma from nevus, we determined the TERT promoter mutation status of 86 primary melanomas, 72 melanocytic nevi and 40 diagnostically problematic melanocytic proliferations. Of the 86 melanomas, 67 (77.9%) were TERT-positive, defined as harboring a hotspot TERT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 33 publications
(57 reference statements)
1
35
0
Order By: Relevance
“…87 In different melanocytic neoplasms, the TERT promoter mutations serve as ancillary tools for ambiguous histological tumors because of their high specificity for melanoma and absence in melanocytic nevi and melanocytes adjacent to the tumors. 64,[108][109][110][111] In bladder cancer, besides being associated with an increased disease recurrence and poor patient outcome, the specificity of the TERT promoter mutations distinguishes histologically deceptive cancers from benign mimics. 88,112 The TERT promoter mutations associated with high disease grades and the worst patient survival in gliomas and together with other markers follow histological classification into subgroups with distinct outcomes.…”
Section: Impact Of Tert Promoter Mutationsmentioning
confidence: 99%
See 1 more Smart Citation
“…87 In different melanocytic neoplasms, the TERT promoter mutations serve as ancillary tools for ambiguous histological tumors because of their high specificity for melanoma and absence in melanocytic nevi and melanocytes adjacent to the tumors. 64,[108][109][110][111] In bladder cancer, besides being associated with an increased disease recurrence and poor patient outcome, the specificity of the TERT promoter mutations distinguishes histologically deceptive cancers from benign mimics. 88,112 The TERT promoter mutations associated with high disease grades and the worst patient survival in gliomas and together with other markers follow histological classification into subgroups with distinct outcomes.…”
Section: Impact Of Tert Promoter Mutationsmentioning
confidence: 99%
“…A study to measure the effect of individual TERT promoter alterations showed that the less frequent −138/−139CC>TT tandem mutation had the worst impact on disease‐free and melanoma‐specific survival in stage I and II patients 87 . In different melanocytic neoplasms, the TERT promoter mutations serve as ancillary tools for ambiguous histological tumors because of their high specificity for melanoma and absence in melanocytic nevi and melanocytes adjacent to the tumors 64,108‐111 . In bladder cancer, besides being associated with an increased disease recurrence and poor patient outcome, the specificity of the TERT promoter mutations distinguishes histologically deceptive cancers from benign mimics 88,112 .…”
Section: Impact Of Tert Promoter Mutationsmentioning
confidence: 99%
“…Many of the identified noncoding hotspots were located in sequences of genes functionally related to cancer or more specifically to UV radiation-related skin cancers. Some of them were reported before in melanoma or identified by us in melanoma TCGA samples, the cancer type most intensively studied in terms of mutations in noncoding regions [109,110]. Below, we briefly describe the cancer-related role of the three most interesting genes with hotspot mutations in noncoding regions, i.e., BAD , DHODH , and CHCHD2 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that noncoding mutations in only the promoters of TERT and DPH3 were previously analyzed in BCC [27,135,136]; TERT and DPH3 are known to be mutated in many cancers, including melanoma [109,110]. However, as our WES design generally did not cover promoter regions, we did not look for or detect these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In different melanocytic neoplasms, the TERT promoter mutations serve as ancillary tools for ambiguous histological tumors because of their high specificity for melanoma and absence in melanocytic nevi and melanocytes adjacent to the tumors 64,[108][109][110][111] . In bladder cancer, besides being associated with an increased disease recurrence and poor patient outcome, the specificity of the TERT promoter mutations distinguishes histologically deceptive cancers from benign mimics 88,112 .…”
Section: Impact Of Tert Promoter Mutationsmentioning
confidence: 99%